2023
DOI: 10.1111/imr.13230
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the IL‐4/IL‐13 axis for targeted immune modulation

Abstract: SummaryThe structurally and functionally related interleukin‐4 (IL‐4) and IL‐13 cytokines play pivotal roles in shaping immune activity. The IL‐4/IL‐13 axis is best known for its critical role in T helper 2 (Th2) cell‐mediated Type 2 inflammation, which protects the host from large multicellular pathogens, such as parasitic helminth worms, and regulates immune responses to allergens. In addition, IL‐4 and IL‐13 stimulate a wide range of innate and adaptive immune cells, as well as non‐hematopoietic cells, to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 307 publications
0
16
0
Order By: Relevance
“…IL-4 can be produced by activated CD4 + T cells, CD4 + NK1.1 + natural killer T (NKT) cells, group 2 innate lymphoid cells (ILC2s), macrophages, eosinophils, basophils, and mast cells. IL-4 plays a significant role in regulating immune activity and is crucial for the development of Th2-mediated responses ( 43 ). Previous studies have found that NLRP3 protein can activate Th2 cells ( 44 ) through IL-4 and promote M2 macrophage polarization ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-4 can be produced by activated CD4 + T cells, CD4 + NK1.1 + natural killer T (NKT) cells, group 2 innate lymphoid cells (ILC2s), macrophages, eosinophils, basophils, and mast cells. IL-4 plays a significant role in regulating immune activity and is crucial for the development of Th2-mediated responses ( 43 ). Previous studies have found that NLRP3 protein can activate Th2 cells ( 44 ) through IL-4 and promote M2 macrophage polarization ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The receptor chains lack endogenous kinase activity and thus utilize receptor-associated kinases, such as the Janus family tyrosine kinases (JAKs) and others, for signal transduction. The main signaling pathways activated by IL-13Rα1 and IL-4Rα chain heterodimerization are the JAK/STAT pathway, the IRS pathway, and the SHP-1/SHP-2/SHIP pathway [ 99 ]. Among them, STAT6 is the major transcription factor pathway activated in response to IL-4 and IL-13 binding, and STAT6 phosphorylation is crucial for the expression of IL-4 and IL-13 target genes [ 98 , 99 , 100 , 101 , 102 ].…”
Section: Cytokine/chemokine Axes Functionally Relevant In Mfmentioning
confidence: 99%
“…The main signaling pathways activated by IL-13Rα1 and IL-4Rα chain heterodimerization are the JAK/STAT pathway, the IRS pathway, and the SHP-1/SHP-2/SHIP pathway [ 99 ]. Among them, STAT6 is the major transcription factor pathway activated in response to IL-4 and IL-13 binding, and STAT6 phosphorylation is crucial for the expression of IL-4 and IL-13 target genes [ 98 , 99 , 100 , 101 , 102 ]. The IRS-2/PI3K/AKT/mTOR pathway contributes additional transcriptional modulation mainly through AKT-dependent activation of FoxO1, Bad, TOR, and NF-κB.…”
Section: Cytokine/chemokine Axes Functionally Relevant In Mfmentioning
confidence: 99%
See 1 more Smart Citation
“…The proinflammatory cytokine IL-13, which was identified in 1989, has a very broad spectrum of action. A recent review [ 16 ] explains the importance and function of IL-13 for the regulation of immunoglobulins (Ig), inflammation, anti-parasitic reactions, fibrogenesis, and allergic reactions. IL-13 can also be released as a preform by granulocytes such as basophils, mast cells, or eosinophils, a process in which IgE plays an important role [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%